2022
DOI: 10.3390/metabo12111041
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Response throughout 16 Weeks of Combined Aerobic and Resistance Exercise Training in Older Women with Metabolic Syndrome

Abstract: Increases in longevity and obesity have led to a higher prevalence of Metabolic Syndrome (MetS) and several chronic conditions, such as hypertension. The prevalence of MetS and hypertension increases with advancing age and their detrimental effects on health can be attenuated by physical activity. Combined aerobic and resistance exercise training (CT) is recommended to maintain good health in older adults and is known to generate important metabolic adaptations. In this study we performed a metabolomics analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…valine metabolism, respectively [79]. The studies reporting the metabolic changes associated with combined chronic endurance-resistance training are summarized in Table S7 [39].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…valine metabolism, respectively [79]. The studies reporting the metabolic changes associated with combined chronic endurance-resistance training are summarized in Table S7 [39].…”
Section: Discussionmentioning
confidence: 99%
“…During chronic combined endurance–resistance exercise, several studies showed alterations of lipid metabolism [ 37 , 38 , 73 , 78 , 79 , 80 , 81 , 82 ]. These included alterations of certain phospholipids, diacylglycerols, ceramides, acylcarnitines, cardiolipins, cortisols, ketone bodies, HDLs, and unsaturated fatty acids.…”
Section: Metabolic Signature Of Combined Endurance and Resistance Exe...mentioning
confidence: 99%
See 3 more Smart Citations